On analysis of entropy measures for titanium dioxide via rational curve fitting methods. Issue 23 (16th August 2022) - Li, Cheng‐Peng; Siddiqui, Muhammad Kamran; Ali, Parvez; Javed, Sana; Hussain, Mazhar; Khalid, Sadia
Abstract: In chemical graph theory, graph entropy is an essential parameter. It measures chemical graphs and complicated networks. In discrete mathematics, biology, and chemistry, graph entropy measures have specialized chemical uses. The purpose of this paper is to discuss graph entropies and the structure of Titanium dioxide ( TiO 2 ). We developed a new idea of computing entropies of titanium dioxide based on the degree of end vertices. Moreover, we have computed graph entropy indices for real systems, and made correlations with thermodynamic quantities like heat of formation and (thermodynamic) entropy. Also, curves have been fitted between entropy indices and thermodynamics properties (entropy, enthalpy) rational method using MATLAB. Abstract : Crystallographic structure of (a) rutile and, (b) anatase titanium atoms (white) and oxygen atoms (red) form TiO6 polyhedra in the lattices. In communication theory, graph entropy is an essential parameter. It measures chemical graphs and complicated networks. In discrete mathematics, biology, and chemistry, graph entropy measures have specialized chemical uses. The purpose of this paper is to discuss graph entropies and the structure of titanium dioxide (TiO2 ). Moreover, entropies of titanium dioxide based on the degree of end vertices have been calculated. Also, curves have been fitted between entropy indices and thermodynamics properties (entropy, enthalpy) rational method in MATLAB.